How to Express Boredom via Intonation in Kurdish with Special Reference to English - Al-Bazzaz , Safwat H; Qadir, Sarkawt Muhammad (Journal of Ecohumanism, 2024)
The present study examines the contribution of intonation to the vocal expressions of boredom in utterances. It begins by providing a theoretical overview of the role intonation plays in conveying emotions or attitudes. Further, it outlines the tonetic aspects, pitch characteristics, and other prosodic factors that participate in conveying boredom in English depending on the literature available. The study then turns to analysing sixteen tone groups taken from four Kurdish films and recorded materials of everyday spoken Kurdish. It tests and underscores the tonetic aspects and pitch characteristics of these chosen tone groups used for the expression of boredom, relying on six parameters, namely the syntactic category, the height of the pre-head, the height of the head, the tone used, the pitch range, and the key. The role of all these intonation factors is investigated. Special reference is also made to other factors such as loudness, speed of speaking, and paralinguistic features. The work shows that the cues used to convey boredom vary, although pitch and pitch variation become dominant and central. Among all the intonation cues used to express boredom, pitch range, and tone are the most relevant and useful cues.